Circular Bioeconomy Innovation Hub: the case of Ghana. Annual report 2023 - Agbefu, Dzifa; Amoah, Philip (International Water Management Institute (IWMI). CGIAR Initiative on Resilient Cities; CGIAR Initiative on Nature-Positive Solutions, 2023)
In response to the escalating waste management challenges triggered by rapid urbanization and its effects on resource use and the environment a Circular Bioeconomy Innovation Hub (CBE-IH) has been set-up in Ghana, under the leadership and facilitation of the International Water Management Institute (IWMI) with the support of CGIAR Initiatives Resilient Cities and Nature Positive Solutions. Operating within the organic waste to resource value chain, the CBE-IH operates on co-ownership principles with 16 stakeholders from the public and private sectors, research institutions, NGOs, and the education sector. With jointly defined objectives and workplan, the co-owners have joined forces, contributing resources for co-design and co-implementation to achieve shared impact. Beyond being a showcase of circular bioeconomy innovations, the CBE-IH serves as a one-stop-shop for training, advisory, demonstration, and research. It unites key stakeholders in the circular bioeconomy space for accelerated progress aimed at nurturing and advancing the development of new and accessible innovations. To achieve this, five strategic operational areas have been defined for activity development and implementation. These areas aim to enhance the skills and knowledge of circular bioeconomy value chain actors, improve competencies, nurturing change champions, integrating circular concepts into school curricula, and promoting knowledge sharing and collaboration among stakeholders. Fueling these initiatives is a resource pooling strategy from co-owners, where the hub has amassed an array of resources, including training centers with associated expertise, meeting venues, and demonstration sites. This strategy has culminated in the formation of a team comprising 41 trainers. These trainers possess cross-cutting expertise in 12 specialized areas central to the circular bioeconomy domain, encompassing everything from product development and production to business and financial model development, green financing strategies, partnerships, stakeholder engagement, quality management, health and safety, innovation scaling, and gender diversity and inclusion. But what sets the CBE-IH apart is delivery training beyond virtual platforms. The hub's innovative approach extends to practical, hands-on sessions conducted at its 7 "living labs" across the country, hosted by co-owning circular economy businesses. These living labs provide practical settings, facilitating hands-on training on the transformation of organic waste into safe compost, co-compost (with fecal sludge), briquettes, biochar, biogas, black soldier fly cultivation for animal feed, and innovative ventures like aquaculture in symbiosis with wastewater treatment plants. Despite launching in mid-2023, the CBE-IH has already facilitated knowledge transfer training for representatives from five institutions in the operationalization of a 1000-ton/year non-carbonized briquette machine. Additionally, resource recovery and reuse awareness initiatives in pre-tertiary schools have trained 5,489 pre-tertiary school children in 10 schools of which 2,802 are boys and 2687 are girls. While the HUB is currently compiling its website and value proposition (living lab types and locations, training offer), one of the scaling partners of the Hub, the Ministry of Sanitation and Water Resources, involved the Hub in the review process of the National Sanitation Policy, which is well aligned with the operational areas of the hub.